Biodegradability Potential Measurement of Organic Waste to Enhance Compost Quality - Budiarti, Gina; Kamali, Siti Raudhatul; Widiyanti, Astrini; Ernawati, Ernawati; Harfadli, Muhammad Ma'arij (Universitas Diponegoro, 2026)
This study aims to analyze the volume, weight, composition of organic waste, the characteristics of C/N, moisture content, and biodegradability fraction as a reference for biodegradability potential. Using the load count analysis method—based on modifications of SNI 19-3964-1994 and the UN-Habitat Wise Waste Cities Tools (2010)—researchers measured the daily waste generation, which amounted to approximately 11,967±2,528 liters in volume and 1.91±0.4 tons in weight. The organic waste primarily consisted of dry leaves (53%), household waste (25%), green manure and grass (17%), and vegetable waste (5%). Laboratory tests revealed the waste had a carbon-to-nitrogen (C/N) ratio of 62.07%, a moisture content of 66.76%, and a biodegradability fraction of 7.6%. These values do not align with raw material composting standards, indicating the need for waste treatment before composting. To enhance the composting process, the study recommends separating green (nitrogen-rich) and brown (carbon-rich) materials, prioritizing the green portion as the main composting input, and drying the material initially to reduce moisture to 40–45%. Composting is highlighted as a simple, eco-friendly solution for managing organic waste, contributing to soil fertility, structure improvement, and supporting sustainable agricultural practices.